ANALISIS NILAI MORAL DALAM NOVEL RUMAH UNTUK ALIE KARYA LENN LIU - Sesilia Sesilia; La Ode Sahidin; La Ode Adili (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
The purpose of this study is to describe the moral values in the novel House for Alie by Lenn Liu. The type of research is library research. The method used in this study is a qualitative descriptive method. The data in this study is written data, namely excerpts from stories related to moral values in the novel House for Alie by Leen Liu. The source of data in this study is a novel entitled House for Alie by Leen Liu which was published by the media crater in 2024 with a thickness of 262 pages. The data collection technique used in this study is the reading and recording technique. The data analysis technique used in this study is qualitative descriptive. The results of the study show that there are moral values, namely the moral value of human relations with themselves, the moral value of human relations with fellow humans, and the moral value of human relations with God. The moral value of human relationships with oneself is self-esteem, self-confidence, fear, longing, loneliness, responsibility to oneself, obligation to oneself, and manners. Furthermore, the moral value of human relationships with fellow humans is to think positively, help others, help selflessly and respect each other. Then, the moral value of human relations with God is surrender and obedience to God, praying or begging God, and acknowledging God's greatness.